Strengthening democracy through meaningful participation in the legislative process in Indonesia - Zuhdi, Achmad; Agustina, Enno Sellya; Kamula, Ari Ade (DIXI, 2025)
This research examines the concept of meaningful public participation in the legislative process in Indonesia, emphasizing its importance in achieving democratic governance and ensuring legislation reflects the people’s will. The study uses a normative legal research method, analyzing laws and doctrines related to participatory democracy and the principles of public involvement. The findings highlight that public participation in Indonesia remains limited to consultative and informative levels, as reflected in the legislation process regulated by Law No. 12 of 2011 and its amendments. The study identifies gaps in implementation and proposes adopting principles from deliberative democracy and public participation theories to enhance legislative inclusiveness and effectiveness. The research concludes that meaningful participation requires clear mechanisms and parameters to balance legislative decision-making with public aspirations.
Keywords: Meaningful participation; public involvement; legislative process; deliberative democracy